2012
DOI: 10.2215/cjn.03720412
|View full text |Cite
|
Sign up to set email alerts
|

Bully Renal Cysts Knock Down Urine-Concentrating Capacity in the Early Rounds

Jared J. Grantham

Abstract: The commonly accepted manifestations of renal insufficiency are usually not recognized in patients with autosomal dominant polycystic kidney disease (ADPKD) until the fourth decade of life (1). However, many ADPKD patients with GFRs indistinguishable from normal are unable to increase the osmolality of urine above 800 mosm/kg H 2 O after overnight dehydration or after the parenteral administration of supplementary vasopressin. This "concentrating defect" can be detected in some young children and young adults … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…In our previous study [6] along with further pediatric and adult studies [5,7,8,20,21], it has been shown that approximately 50% of patients with ADPKD have impaired kidney concentrating ability and reduced concentration capacity. These impairments were linked to ambulatory BP and the number of kidney cysts, but not to GFR.…”
Section: Age ( Years )mentioning
confidence: 99%
“…In our previous study [6] along with further pediatric and adult studies [5,7,8,20,21], it has been shown that approximately 50% of patients with ADPKD have impaired kidney concentrating ability and reduced concentration capacity. These impairments were linked to ambulatory BP and the number of kidney cysts, but not to GFR.…”
Section: Age ( Years )mentioning
confidence: 99%